Intermetallic Phase on the Interface of Ag-Au-Pd/Al Structure. (13th March 2014) - Hsueh, Hao-Wen; Hung, Fei-Yi; Lui, Truan-Sheng; Chen, Li-Hui; Chen, Kuan-Jen
Abstract : Three wires, Au, Cu, and Ag-Au-Pd, were bonded on an Al pad, inducing IMC growth by a 155 hr high temperature storage (HTS) so that the electrical resistance was increased and critical fusing current density (CFCD) decreased. Observations of the Ag-Au-Pd wire after HTS (0–1000 hr) indicated that IMC between the Ag-Au-Pd wire and Al Pad was divided into three layers: Ag2 Al layers above and below the bonding interface and a polycrystal thin layer above the total IMC. A high percentage of Pd and Au existed in this 200 nm thin layer, and could suppress Al diffusion into the Ag matrix to inhibit IMC growth. After PCT-1000 hr, a noncontinuous structure still remained between the IMC layer and interface, and the main phase of IMC was (Ag, Au, Pd)2 Al with a hexagonal structure.